THE RELATIONSHIP OF KNOWLEDGE AND ATTITUDE OF 2019S CLASS BATCH STUDENTS OF THE FACULTY OF MEDICINE UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA ON WOUND HEALING WOUNDED BY ALOE VERA GEL (ALOE VERA) - Sembiring, Ranggi Heryagung; Yenita, Yenita (Medicina Biomedica Journal, 2023)
Introduction: Wounds are still a public health problem. Various ways are done by humans to treat wounds such as using modern medicine and traditional medicine, one of the traditional medicines to treat wounds is aloe vera gel (aloe vera), where aloe vera gel is already available in packaged form. Human knowledge is based on curiosity, effort in finding out and from experience. Attitude is an action but is a predisposition to the action of a behavior. Purpose: To determine the relationship between knowledge and attitudes of 2019s Class Batch Students of the Faculty of Medicine, Universitas Muhammadiyah Sumatera Utara regarding to Wound Healing Given Aloe Vera Gel (Aloe Vera). Methods: This research uses a descriptive analytic method using a cross sectional approach that uses a questionnaire as a research instrument. The sample used was 2019s class batch UMSUs Medical Students with consecutive sampling technique. Results: Research shows that the level of knowledge of medical students in the Class of 2019 has a good category of 62 respondents (91.0%), in the sufficient category as many as 3 respondents (4.5%) and in the less category as many as 3 respondents (4.5%), based on the attitude category positive as many as 61 respondents (91.0%) and negative category as many as 6 respondents (9.0%). Conclusion: On average, the 2019s class batch students of UMSUs Faculty of Medicine have good knowledge and positive attitudes towards aloe vera gel with wound healing.